Oscillation of metastable population and slow light propagation in a Tm3+ -doped optical fiber. (19th December 2017) - Qiu, Wei; Wang, Yuda; Liu, Jianjun; Yang, Yujing; Gao, Yuan; Lv, Pin; Jiang, Qiuli
Abstract: The relationship between the oscillation of a metastable population and the slow light propagation in a Tm 3+ -doped optical fiber at room temperature is discussed. We study the influencing factors of the metastable population oscillation, such as the length of the Tm 3+ -doped fiber, the input signal power and the pump power. Further, we obtain the relationships between the length of the Tm 3+ -doped optical fiber, the input signal power and the pump power and the oscillation of metastable population in order to slow down the light pulse propagation speed through an optical fiber at room temperature.